Academic success in a pre-degree programme: a study of students in the Faculty of Education, Universiti Teknologi MARA / Lee Lai Fong, Marina Mohd. Arif and Richard Holmes - Lee, Lai Fong; Mohd. Arif, Marina; Holmes, Richard (ACRULeT, Faculty of Education & UiTM Press, 2006)
This study examines the relationship between pre-admission scores, including interview and placement test results, and academic performance, indicated by Cumulative Grade Point Average, of students in a pre-degree TESL programme. It was found that the correlation between pre-admission scores and academic performance was very slight, in part perhaps because of the restricted range of the CGPA scores. However, it was noted that accuracy and clarity of voice, and SPM scores for chemistry were modestly predictive of academic success and of marginal statistical significance. It is likely, therefore, that communication skills in English and general cognitive ability spanning arts and science subjects make the greatest contribution to success in this programme.